Herbal medicine, Banxia-xiexin tang, for functional dyspepsia: a systematic review and meta-analysis - Kim, Keumji; Ko, Seok-Jae; Cho, Soo Ho; Kim, Jinsung; Park, Jae-Woo (Frontiers in Pharmacology, 2023)
Background: The demand for complementary and alternative medicine for the management of functional dyspepsia (FD) is increasing due to the insufficient efficacy of conventional treatment options. In Asia, the Chinese herbal medicine formula Banxia-xiexin tang (BXT) has been used to treat FD. Methods: We searched 11 digital medical databases on September 1, 2021. Randomized controlled trials (RCTs) that investigated the efficacy of BXT or combination therapy (BXT plus Western medicines) for FD were selected. The outcome parameters were total clinical efficacy rate (TCE), motilin level, symptom checklist-90-revised (SCL-90-R), and visual analog scale (VAS) for dyspepsia and adverse events. Cochrane risk of bias tool 2.0 (RoB 2) was used for the quality assessment of included studies. Results: The meta-analysis comprised 57 RCTs with 5,525 participants. BXT was more efficacious, with a higher TCE than Western medicine. Combination therapy (BXT plus Western medicine) also resulted in a higher TCE than Western medicine. Combination therapy improved motilin levels and psychological symptoms to a greater extent than Western medicine, evidenced by a higher SCL-90-R score. However, no significant difference in VAS scores was observed between the BXT and placebo groups. BXT and combination therapy were associated with fewer adverse events than Western medicine or placebo. Conclusion: Our findings suggest that BXT and its combination therapy may be an effective and safe alternative treatment for FD. More RCTs with better methodologies are required to strengthen this evidence.